Thyroid hormone regulation of heme oxidation in the liver. - Smith, T J (1982)
The effects of 3,5,3'-triiodothyronine (T3) on heme oxygenase (EC 1.14.99.3) activity and cytochrome P-450 content in liver were examined in thyroidectomized rats. T3, when administered for 5 days at a dose of 6 micrograms/100 g of body weight, stimulated basal heme oxygenase activity approximately equal to 2-fold compared to diluent-treated animals. The induction of heme oxygenase by cobalt heme also was enhanced approximately equal to 3-fold in T3-treated animals. T3 treatment lowered cytochrome P-450 content by approximately equal to 50% and potentiated the depletion of this heme protein after cobalt heme administration. Reverse T3 had no effect either on cytochrome P-450 content or on heme oxygenase activity in liver. The time course of response to a single dose of T3 (50 micrograms/100 g of body weight) revealed that both basal and cobalt heme-induced heme oxygenase activity peaked at 48 hr and that cytochrome P-450 content declined to approximately equal to 40% of controls at 96 hr. Examination of microsomal proteins by polyacrylamide gel electrophoresis after T3 treatment disclosed that major bands in the Mr approximately equal to 50,000-55,000 region were diminished. The administration of T3 together with SKF-525A, a compound known to complex with the heme prosthetic group of cytochrome P-450, resulted in partial preservation of these proteins. These data indicate that thyroid hormone can regulate heme oxygenase activity and concomitantly can lower cytochrome P-450 content in liver. The hormone also can act in a synergistic fashion to enhance the response of hepatic heme oxygenase to a chemical inducer of the enzyme. Thyroid status thus may be a potentially significant determinant of the rate of heme oxidation in the liver.